Solution-phase synthesis and thermal conductivity of nanostructured CdSe, In2Se3, and composites thereof1. Issue 25 (7th July 2015) - Ma, Yuanyu; Liu, Minglu; Jaber, Abbas; Wang, Robert Y.
<x xml:space="preserve">Abstract</x> We synthesize and characterize nanoparticle-in-matrix composites. These crystalline inorganic nanocomposites have very low thermal conductivities comparable to amorphous polymers.